Peluang dan Tantangan Guru Sosiologi dalam Menghadapi Kurikulum “Merdeka Belajar” di Era Revolusi Industri 4.0: Sociology Teachers’ Opportunities and Challenges in Facing “Merdeka Belajar” Curriculum in the Fourth Industrial Revolution (Industry 4.0) - Yuhastina Yuhastina; Bagas Narendra Parahita; Dwi Astutik; Ghufronudin Ghufronudin; Danang Purwanto (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2020)
This study aims to analyze the opportunities and challenges of Merdeka Belajar as a national education program for high school teachers nationally. Teachers’ problem in implementing Merdeka Belajar (Freedom of Learning) curriculum lacks understanding of the procedures. This happened because there was no structural explanation regarding the differences between the curriculum they had been running so far and Merdeka Belajar curriculum. Many problems arise when implementing the curriculum that the education they have been running has made students dependent. In this context, this study questions how high school sociology teachers’ opportunities and challenges in facing Merdeka Belajar curriculum in the fourth industrial revolution (industry 4.0)? This study aims to identify problems and strategies for teachers in facing the new paradigm of Merdeka Belajar. This study’s analysis is based on theories such as those from Neill, Rogers, Freire, Boal, Giroux, and Knowles to critically analyze the pedagogical paradigm of national education that teachers have used. This study uses Knowles’s theory of andragogy to explore the notion of Merdeka Belajar. This study’s qualitative research method includes observation of the teacher-student relationship and interviews with several high school teachers in Karanganyar, Central Java. Besides, document studies related to Merdeka Belajar program are also used to understand the policy context. This study found that teachers did not realize that they had been using a pedagogical paradigm (education for children) for high school-level children who had grown up. When they switched to Merdeka Belajar curriculum, they also did not know that the paradigm they should be using is andragogy (education for adults). In this situation, they improvised as best they could to implement Merdeka Belajar. The teachers only carry out orders from the school. However, the school is still trying to understand how it works based on structural orders without clarity. Students’ dependence on teachers has become the cause of teachers’ difficulty to move out of the pedagogical paradigm into andragogy. In this situation, the teachers tried to do their best to implement Merdeka Belajar program during the Covid-19 pandemic. Teachers and schools must also face all infrastructural barriers and socioeconomic conditions with limited online learning access.